Comparison of carbon dots prepared from collagen peptides using conventional hydrothermal and microwave methods. (19th January 2023) - Xu, Chengzhi; Kang, Jizhen; Zhao, Yanqiu; Zhu, Lian; Zhang, Juntao; Wei, Benmei; Wang, Haibo
Abstract : Differences between CDs prepared by microwave reaction and conventional hydrothermal methods were systematically compared to guide the optimization of the reaction parameters of biomass-derived CDs. Abstract : Fish scale collagen peptides were used as a precursor to prepare carbon dots using conventional hydrothermal (CDs-HT) and microwave (CDs-MW) methods. The optical properties of CDs prepared using the two methods were compared and the influence of the heating method on the structure of CDs was analyzed. Both CDs emitted blue fluorescence and exhibited an excitation-dependent emission character. The rapid and uniform heating during the microwave method is more conducive to the self-doping of nitrogen. Although CDs-HT have a lower doping amount of nitrogen, the relative content of pyrrolic N is higher. In contrast to the limited sealing of the microwave reaction vessel, the controllable high-temperature sealing environment of the conventional hydrothermal method could promote complete dehydration and condensation of the precursor to form smaller-sized CDs. Therefore, in comparison to CDs-MW, CDs-HT exhibited a higher quantum yield (9.29% versus 4.86%).